2017
DOI: 10.1038/am.2017.179
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical half-reaction-assisted sub-bandgap photon sensing in a graphene hybrid phsotodetector

Abstract: The photogating effect has been previously utilized to realize ultra-high photoresponsivity in a semiconductor-graphene hybrid photodetector. However, the spectral response of the graphene hybrid photodetector was limited by the bandgap of the incorporated semiconductor, which partially compromised the broadband absorption of graphene. Here, we show that this limitation can be overcome in principle by harnessing the electron-accepting ability of the electrochemical half-reaction. In our new graphene phototrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Nanoparticles have recently gained prominence as advanced drug delivery systems in the biotechnology and pharmaceutical industries. In the context of GF immobilization, nanoparticles can be loaded with GFs, facilitating controlled delivery (Wang et al, 2017). For instance, VEGF was loaded into dermatan sulfate sodium salt-poly-l-lysine (DS-PLL) and gum tragacanthpoly-l-lysine (GT-PLL) nanoparticles with loading efficiencies of 93.1 and 80.2%, respectively (Zandi et al, 2020).…”
Section: Physical Encapsulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanoparticles have recently gained prominence as advanced drug delivery systems in the biotechnology and pharmaceutical industries. In the context of GF immobilization, nanoparticles can be loaded with GFs, facilitating controlled delivery (Wang et al, 2017). For instance, VEGF was loaded into dermatan sulfate sodium salt-poly-l-lysine (DS-PLL) and gum tragacanthpoly-l-lysine (GT-PLL) nanoparticles with loading efficiencies of 93.1 and 80.2%, respectively (Zandi et al, 2020).…”
Section: Physical Encapsulationmentioning
confidence: 99%
“…The properties of materials and solutions used to immobilize the GF can be tuned to control adsorption (King and Krebsbach, 2012). Some of the disadvantages of this approach are low loading efficiency, poor control over release, and minimum spatial control (Midy et al, 1998;Budiraharjo et al, 2013;Wang et al, 2017). This approach has been utilized to immobilize different types of GFs, including BMP-2, FGF, and FGF-2 (Ziegler et al, 2008;Budiraharjo et al, 2013).…”
Section: Surface Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, owing to the efficient separation of the charge carriers at the interface, the response rates of the HPs are accelerated, and a τ rise value of 92 ms can be realized, but τ rise and τ decay of the HPs are extended to some extent with the rising concentration. Many reports have shown that the generation process of the high photocurrent helps to prolong the carrier lifetime, τ lifetime . On the other hand, the high carrier mobility in the high‐quality channel contributes to a shorter carrier transit time, τ transit .…”
Section: Resultsmentioning
confidence: 99%